Imam Ghazali’s rational approaches in his book Al-Mustasfa – An empirical and analytical study - Al-Jabr, Nayef AbdulRahman; Al-Harbi, Hind Saad (Journal of Islamic Sciences, 2023)
This research aims to identify the rational approaches in Imam Ghazali’s book Al-Mustasfa and outlines the unique classification adopted by Imam Ghazali as well as highlighting his rational methodology and its overall impact and influence. The theoretical underpinning of this study is based on examining the rational approaches to Ghazali’s seminal book, Al-Mustasfa and relies on the analytical method to probe Ghazali’s methodology and its influence on the field. This research focuses on the rational approaches adopted by Imam Ghazali, their causes and effects and his critics and proponents of these approaches. Some of the most prominent approaches include: Classification of scientific disciplines, Conceptual framework of theoretical disciplines by limiting them to tools such as Had and evidence-based reasoning, Classification of major research tools, Different types of Had. This research concludes that Imam Ghazali was a pioneer who used rational approaches before other scholars and shows the connection of these rational approaches to the discipline of Usool Al-Fiqh.